2014
DOI: 10.1007/s13197-014-1590-5
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiation and magnetic field mediated delay in effect of accelerated ageing of soybean

Abstract: Soybean seeds were exposed to gamma radiation (0.5, 1, 3 and 5 kGy), static magnetic field (50, 100 and 200 mT) and a combination of gamma radiation and magnetic energy (0.5 kGy+200 mT and 5 kGy+50 mT) and stored at room temperature for six months. These seeds were later subjected to accelerated ageing treatment at 42°C temperature and 95-100 % relative humidity and were compared for various physical and biochemical characteristics between the untreated and the energized treatments. Energy treatment protected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Similar statistically insignificant effects in terms of increased protein content in leaves in two cultivars: MERLIN and ANUSZKA, induced by alternating the magnetic field, were obtained in our research. In turn, Kumar et al 74 , after stimulating soy seeds stored for 6 months with CMF, observed elevated protein concentration in the yield as compared to the control, which is consistent with our results obtained for the MAVKA, MERLIN, and ANUSZKA cultivars where the CMF was found to have the highest positive influence relative to the control. Magnetic fields with low induction values facilitate intensified binding or breakup of proteins in plant roots to a greater extent than in seedlings 28 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Similar statistically insignificant effects in terms of increased protein content in leaves in two cultivars: MERLIN and ANUSZKA, induced by alternating the magnetic field, were obtained in our research. In turn, Kumar et al 74 , after stimulating soy seeds stored for 6 months with CMF, observed elevated protein concentration in the yield as compared to the control, which is consistent with our results obtained for the MAVKA, MERLIN, and ANUSZKA cultivars where the CMF was found to have the highest positive influence relative to the control. Magnetic fields with low induction values facilitate intensified binding or breakup of proteins in plant roots to a greater extent than in seedlings 28 .…”
Section: Resultssupporting
confidence: 92%
“…Electrons with magnetic moments may be oriented in the outer field whose energy is absorbed due to interactions between the field and the magnetic moment of the unpaired electrons. Since chloroplasts have their own magnetic moments, it is possible that under the influence of large doses of absorbed energy, a distortion of photosynthetic pigment synthesis may occur 73 , 74 .…”
Section: Resultsmentioning
confidence: 99%
“…The stimulatory response of pulsed magnetic field (PMF) seed treatment on plant growth and development has also been reported in soybean (Radhakrishnan and Ranjitha Kumari 2012). In our previous study, static magnetic field delayed ageing in soybean under accelerated ageing and maintained its quality (Kumar et al 2014). We also reported reclamation of six year old aged pea seeds stored under controlled conditions by using static magnetic field .…”
Section: Introductionmentioning
confidence: 64%